2011
DOI: 10.1007/s00404-011-2176-3
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of pregnancies complicated by hyperemesis gravidarum

Abstract: Hyperemesis gravidarum is not associated with adverse pregnancy outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
24
5
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 21 publications
(27 reference statements)
7
24
5
7
Order By: Relevance
“…A link between hyperemesis gravidarum and placental dysfunction disorders was first suggested in a 1991 case-control study reporting a 1.6 times higher risk for preeclampsia in women with severe vomiting [43]. Consistent with our findings, previous studies also showed no increased risks of placenta dysfunction disorders with exposure to hyperemesis [44, 45]. The largest cohort to date with 1,155,033 pregnancies, of which 13,287 were complicated by hyperemesis leading to hospital admission, showed a slightly increased risk for preeclampsia, and a higher risk for pre-term preeclampsia when hyperemesis occurred in the second trimester [15].…”
Section: Discussionsupporting
confidence: 91%
“…A link between hyperemesis gravidarum and placental dysfunction disorders was first suggested in a 1991 case-control study reporting a 1.6 times higher risk for preeclampsia in women with severe vomiting [43]. Consistent with our findings, previous studies also showed no increased risks of placenta dysfunction disorders with exposure to hyperemesis [44, 45]. The largest cohort to date with 1,155,033 pregnancies, of which 13,287 were complicated by hyperemesis leading to hospital admission, showed a slightly increased risk for preeclampsia, and a higher risk for pre-term preeclampsia when hyperemesis occurred in the second trimester [15].…”
Section: Discussionsupporting
confidence: 91%
“…Similar results were reported by Roseboom et al (2011) (comparing 237 HG to 2,190 non-HG women) and by Dodds et al (2006), Bailit et al (2005) and Zhang and Cai (1991). Conversely, data from other authors such as Oguzhan Kuru et al (2012), Bashiri et al (1995) and Hallak et al (1996) suggest that HG is not significantly correlated with adverse pregnancy outcomes and SGA babies. The differences in outcomes reported could be attributed to the differences in population and to how ' smallness ' is defined.…”
Section: Discussionmentioning
confidence: 72%
“…93 Few studies have shown an increased incidence of low birth-weight and prematurity in the babies of these patients. 94,95 The aim of treatment is to ameliorate symptoms, correct dyselectrolytemia and prevent any complications.…”
Section: Hyperemesis Gravidarum (Hg)mentioning
confidence: 99%